The Impact of Gratitude on Connection With Nature: The Mediating Role of Positive Emotions of Self-Transcendence - Chen, Li; Liu, Jiangxin; Fu, Lezhen; Guo, Chang; Chen, Yuhuan (Frontiers in Psychology, 2022)
Gratitude, as one of the positive emotions associated with self-transcendence, is also a moral and pro-social emotion with a pro-social nature. Therefore, in order to verify whether gratitude has the same effect as pro-social in promoting connection with nature, this study (N=890) divided subjects into three groups (gratitude, recreation, and control) and used a questionnaire to explore the effects of gratitude on positive emotions of self-transcendence, connection with nature, and pro-environmental tendencies (willingness to participate in environmental protection, willingness to sacrifice for the environment). The results found that (1) positive emotions of self-transcendence partially mediated the effect of the gratitude condition on connection to nature, and (2) positive emotions of self-transcendence and connection to nature were fully and continuously mediated, suggesting that the gratitude condition had an indirect effect on both (a) willingness to participate in environmental protection and (b) willingness to sacrifice for the environment. These findings imply that we may need to pay more attention to the connection between gratitude and nature to promote a harmonious relationship between humans and nature.